IMPLEMENTATION OF HUMAN RESOURCES DEVELOPMENT AND JOB SATISFACTION AT MA UNGGULANG SYAMSUL ULUM SUKABUMI - Habibie, Dienha; Setiawati, Fenty; Pauzi, Ali Roswan; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyse the implementation of human resource development (HRD) and its impact on job satisfaction at MA Unggulan Syamsul Ulum, Sukabumi. The research method used is qualitative with a case study approach, involving in-depth interviews, observation, and document analysis. The research location was chosen at MA Unggulan Syamsul Ulum because of its relevance to HR development and job satisfaction that has the potential to improve the performance of teaching and education personnel. The results showed that HR development conducted through training, collaboration between senior educators and new educators, as well as competency improvement programmes, contributed significantly to employee job satisfaction. In addition, this study found that high job satisfaction has a positive effect on the motivation and performance of teaching staff. Thus, planned and sustainable HR development is essential to create a productive and satisfying work environment in educational institutions.